An Investigation of Oxidative Stress and Thiol/Disulphide Homeostasis in Graves’ Disease - Veysel Agan; Hakim Celik; Mehmet Ali Eren; Fatma Zehra Agan; Ozcan Erel; Salim Neselioglu; Ismail Koyuncu; Ataman Gonel (Medicina, 2019)
Background and objectives: The aim of this study was to research oxidative stress and thiol/disulphide homeostasis in Graves’ patients. Materials and Methods: The study included 33 Graves’ patients (research group) and 35 healthy subjects (control group). Serum oxidative stress and thiol/disulphide homeostasis (a new and automated spectrophotometric method developed by Erel and Neselioglu) parameters were studied and compared between the groups. Results: The native and total thiol levels and the native thiol/total thiol ratio were lower in patients with Graves’ disease compared to the control group (p < 0.001, p < 0.001, and p = 0.006, respectively). TOS (total antioxidant status), PC (protein carbonyl), OSI (Oxidative stress index), and disulphide/native thiol and disulphide/total thiol ratios were determined to be higher in the Graves’ disease group than in the control group (p < 0.001, p = 0.001, p = 0.001, p = 0.004, and p = 0.006, respectively). In the Graves’ disease group, the free triiodothyronine (FT3) and free thyroxine (FT4) levels were significantly positively correlated with impaired thiol/disulphide homeostasis and oxidative stress parameters (p < 0.05). Conclusion: The results of the current study demonstrated that oxidative stress and thiol/disulphide homeostasis increased towards disulphide formation due to thiol oxidation in Graves’ disease. In addition, a positive correlation of FT3 and FT4 was observed with oxidative stress parameters and impaired thiol/disulphide homeostasis.